2017
DOI: 10.1016/j.msec.2017.03.249
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pore size and porosity on mechanical properties and biological response of porous titanium scaffolds

Abstract: The effect of pore size and porosity on elastic modulus, strength, cell attachment and cell proliferation was studied for Ti porous scaffolds manufactured via powder metallurgy and sintering. Porous scaffolds were prepared in two ranges of porosities so that their mechanical properties could mimic those of cortical and trabecular bone respectively.Space-holder engineered pore size distributions were carefully determined to study the impact that small changes in pore size may have on mechanical and biological b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 150 publications
(86 citation statements)
references
References 40 publications
0
79
0
1
Order By: Relevance
“…In vitro studies reported in the literature revealed that different ranges of porosity can promote different bio‐functions. A recent study showed that Ti scaffolds with pore range between 45 and 106 μm presented the best microarchitecture for early stages of attachment, presenting the higher number of cells, whereas pore range higher than 300 μm exhibited the most favorable conditions for cell proliferation. On the other hand, Hollister stated that macropores up to 1000 μm are crucial for tissue regeneration since they preserve tissue volume, provide temporary mechanical function, and allow the vascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies reported in the literature revealed that different ranges of porosity can promote different bio‐functions. A recent study showed that Ti scaffolds with pore range between 45 and 106 μm presented the best microarchitecture for early stages of attachment, presenting the higher number of cells, whereas pore range higher than 300 μm exhibited the most favorable conditions for cell proliferation. On the other hand, Hollister stated that macropores up to 1000 μm are crucial for tissue regeneration since they preserve tissue volume, provide temporary mechanical function, and allow the vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Prananingrum et al showed that the pore size of 100 µm presented the greatest amount of bone ingrowth, and the rate of bone ingrowth significantly decreased as the pore size increased on Ti scaffolds. Torres‐Sanchez et al concluded that small pores offer a larger surface area and at early days of culture this pore size is favorable for the attachment stage. However, when cell proliferation was dominant, larger pore size ranges also presented the largest growth rate, which confirms that large pore size supports cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Porosity influences cell infiltration, nutrient transfer, tissue growth, and scaffold mechanical properties (Rosa et al, ; Torres‐Sanchez et al, ). Figures and show that the porosity of the scaffold was significantly affected by all four input parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The Taguchi's methods can identify noise sources that affect sample variability and allow to predict and optimize the outcomes without testing all the interactions among inputs (Rao et al, 2008;Taguchi & Yokoyama, 1993 Porosity influences cell infiltration, nutrient transfer, tissue growth, and scaffold mechanical properties (Rosa et al, 2012;Torres-Sanchez et al, 2017). Figures 2 and 3 show that the porosity of the scaffold was significantly affected by all four input parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation